Data-exchange standards and international organizations adoption and diffusion - Thomas, Josephine Wapakabulo, 1976- (Premier reference source., 2010)
"This book seeks to establish the factors and barriers critical to the adoption of data-exchange standards, and ways to accelerate the adoption of these standards"--Provided by publisher.